1973
DOI: 10.1149/1.2403425
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics of Chlorine Evolution and Reduction on Titanium-Supported Metal Oxides Especially RuO[sub 2] and IrO[sub 2]

Abstract: Current‐voltage curves were determined on precious metal oxide‐coated titanium electrodes under conditions relevant to the chlor‐alkali industry. Electrodes in which the oxide coating was of a base metal or only partly of a precious metal were also studied. Clear electrocatalytic effects were found, though in general, linear Tafel behavior was not observed. A possible explanation for the lack of linear Tafel plots in terms of a semiconducting oxide coating was suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1
2

Year Published

1978
1978
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(20 citation statements)
references
References 1 publication
2
15
1
2
Order By: Relevance
“…Studies of selectivity and activity trends on electrodes where the coating composition (Ru:Ti ratio) has been varied in a systematic way are particularly relevant for the present paper. Kuhn and Mortimer [10] found that the anodic exchange current density in NaCl solution was approximately constant down to 20 mol-% Ru content in the mixed coatings. Similar data was presented by Burrows et al [11].…”
Section: Introductionmentioning
confidence: 97%
“…Studies of selectivity and activity trends on electrodes where the coating composition (Ru:Ti ratio) has been varied in a systematic way are particularly relevant for the present paper. Kuhn and Mortimer [10] found that the anodic exchange current density in NaCl solution was approximately constant down to 20 mol-% Ru content in the mixed coatings. Similar data was presented by Burrows et al [11].…”
Section: Introductionmentioning
confidence: 97%
“…They are widely used for the production of chlorine and oxygen and find extensive applications in electroplating, solar cells and supercapacitors [1][2][3][4][5][6][7][8]. For example, they are efficient electrodes for sustaining the oxygen evolution reaction (OER), which is of great importance in water electrolyzers, rechargeable batteries, and zinc, copper, cobalt and nickel electrowinning processes.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical processes do not require elevated temperatures (though they may benefit from them) or the addition of potentially hazardous chemical components, and they are considered less dangerous than non-electrochemical processes (Kuhn & Mortimer, 1973;Schmalz, Dittmar, Haaken, & Worch, 2009). Moreover, they can be tailored to minimize power losses and are well-suited for process automation and control, reducing the need for user intervention (Dominguez-Ramos, Aldaco, & Irabien, 2010).…”
Section: Figure 1 Modular Toilet Designed and Developed By Rti Reseamentioning
confidence: 99%
“…Previous studies have shown that a temperature of 60°C is needed to disinfect E. coli in wastewater by heat alone (Feachem, Bradley, Garelick, & Mara, 1983, p. 232). Separately, other studies have shown that increasing the liquid temperature accelerates electrochemical disinfection and decreases the overpotential at a given current density on metal oxide surfaces (Kuhn & Mortimer, 1973;Schmalz et al, 2009). The electrochemical process explored in this manuscript is intended to be used in a self-contained toilet apparatus where solid waste (feces) will also need to be disinfected.…”
Section: Optimization Of the Mmo Electrode Systemmentioning
confidence: 99%